Imbalance of Cognitive and Psychomotor Assessment on Student Learning Motivation in State High Schools - Rusdiyanti, Rahma Putri; Ilma, Nafiatul; Syaharani, Aurelia; Purwanti, Dita Ayu; Nasrudin, Moh. (Tahta Media Group, 2025)
This study examines the impact of the imbalance between cognitive and psychomotor assessment on student learning motivation at State Senior High School 1 Kajen. Using a qualitative approach, data were collected through observation and interviews with students active in non-academic activities. The data analysis technique used three stages: data reduction, data display, and description/verification of conclusions. The study results indicate that an excessive emphasis on cognitive achievement in the formal assessment system causes students who excel in psychomotor skills to feel unappreciated, negatively impacting their learning motivation. This non-holistic assessment can hinder students' development, especially in character building and life skills. This study emphasises the importance of a balanced educational evaluation system that recognises students' contributions in various domains, both academic and non-academic. The uniqueness of this study lies in its emphasis on the need to redefine indicators of educational success to be more inclusive and humanistic.